Estado brasileiro e “questão ambiental”: ações do governo Bolsonaro para o capital avançar seu controle destrutivo na relação natureza-sociedade - Pereira, Adriana Carla de Jesus (2024)
This dissertation is part of the debate on the interfaces between Society and Nature in capitalism, specifically on the relationship between the Brazilian State and the “environmental issue” in the context of the Bolsonaro government (2019-2022). The general objective is to analyze some interventions by the Bolsonaro government in Brazilian environmental policy. The study aims to highlight how the Bolsonaro administration deepened an offensive to provide greater flexibility in the regulatory frameworks that make up environmental policy to meet the demands of reproducing the capital system in crisis. The research is characterized as bibliographic and documentary, of a qualitative nature. Through the historical-dialectical materialist method, we seek to understand the socio-historical determinants that affect the current situation of environmental destructiveness, located in the dynamics of the structural crisis of capital. Following the theoretical path, we capture the particularities of the Brazilian State through the social and economic formation of Brazil, starting from the conception of totality, the spinal collusion between capital and the State in the destructive processes of nature and exploitation of work. We analyzed normative material, mainly presidential decrees, which affected institutional and administrative changes regarding the preservation and use of the environment. The results indicate that private property, commodity form and labor exploitation are inscribed in the expansive structure of the capital system that increasingly result in human and natural devastation. Mainly they indicate that the Brazilian State, with an autocratic character, operates with policies designed to guarantee the most predatory forms of plundering of natural resources. A trend that deepens with the rise of the extreme right represented by the Bolsonaro government, explicitly in defense of the indiscriminate use of natural resources to feed the greed for profit, using expedients (decrees, provisional measures, curtailing social participation, emptying bodies responsible for environmental inspection) to benefit the fraction of the bourgeoisie linked to agribusiness and mining, important sectors of the national economy. The Bolsonaro government, with fascist aspirations, was the possible option for Brazilian (dependent) capitalism to continue accumulating in the midst of the capital crisis.